Sciatic Nerve Regeneration Using Collagen Tubes and Acellular Nerve Transplants in Rabbits (A comparative study) - Ali Ghanim Abdulla; AbdulJabbar Jameel Al-Samarae; Samira Abdulhussain Abdullah (Tikrit Journal of Pure Science, 2020)
The present study was conducted to evaluate and compare on anatomical bases between the different types of nerve graft, autograft, collagen tubes (natural polymers), and acellular epineurial nerve sheaths (biological conduits), which included acellular rabbit nerve graft and acellular rat nerve graft.